The Role of Mitochondrial Dysfunction in Radiation-Induced Heart Disease: From Bench to Bedside - Livingston, Katie (Front Cardiovasc Med, 2020)
Radiation is a key modality in the treatment of many cancers; however, it can also affect normal tissues adjacent to the tumor, leading to toxic effects. Radiation to the thoracic region, such as that received as part of treatment for breast and lung cancer, can result in incidental dose to the heart, leading to cardiac dysfunction, such as pericarditis, coronary artery disease, ischemic heart disease, conduction defects, and valvular dysfunction. The underlying mechanisms for these morbidities are currently being studied but are not entirely understood. There has been increasing focus on the role of radiation-induced mitochondrial dysfunction and the ensuing impact on various cardiac functions in both preclinical models and in humans. Cardiomyocyte mitochondria are critical to cardiac function, and mitochondria make up a substantial part of a cardiomyocyte's volume. Mitochondrial dysfunction can also alter other cell types in the heart. This review summarizes several factors related to radiation-induced mitochondrial dysfunction in cardiomyocytes and endothelial cells. These factors include mitochondrial DNA mutations, oxidative stress, alterations in various mitochondrial function-related transcription factors, and apoptosis. Through improved understanding of mitochondria-dependent mechanisms of radiation-induced heart dysfunction, potential therapeutic targets can be developed to assist in prevention and treatment of radiation-induced heart damage.